2005
DOI: 10.1056/nejmoa043999
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Thyroidectomy in Multiple Endocrine Neoplasia Type 2A

Abstract: In this study, young patients identified by direct DNA analysis as carriers of a RET mutation characteristic of MEN-2A had no evidence of persistent or recurrent medullary thyroid carcinoma five or more years after total thyroidectomy. A longer period of evaluation will be necessary to confirm that they are cured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
222
1
13

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(243 citation statements)
references
References 21 publications
7
222
1
13
Order By: Relevance
“…• For carriers of high-and moderate-risk mutations (ATA categories H and MOD; classic and atypical MEN2A), nodal spread is very rarely present before the age of 10 years (Skinner et al 2005, Elisei et al 2012.…”
Section: Transformation Of the Thyroid Glandmentioning
confidence: 99%
“…• For carriers of high-and moderate-risk mutations (ATA categories H and MOD; classic and atypical MEN2A), nodal spread is very rarely present before the age of 10 years (Skinner et al 2005, Elisei et al 2012.…”
Section: Transformation Of the Thyroid Glandmentioning
confidence: 99%
“…This is the case with the use of prophylactic thyroidectomy for persons with pathogenic RET mutations because family studies have demonstrated previously a high penetrance for these mutations 55 . Additionally, a recent review indicates that requiring RCTs in conjunction with current evidence-based medicine classification of data quality to assess diagnostic criteria is inadequate, proposing that alternative scales are needed to determine the value of pathology results outside of the limited scope of evaluating RCT drug trial outcomes for prognostic and predictive data 56 .…”
Section: Recommendations Alternatives To Randomized Controlled Trialsmentioning
confidence: 99%
“…MTC may occur sporadically (in about 75% of cases) or as a part of the autosomal dominantly inherited cancer syndrome, known as multiple endocrine neoplasia type 2 (MEN 2) (Mulligan et al, 1993;Eng, 1999;Frank-Raue et al, 2007). MTC is the most common cause of death in patients with MEN 2 (Skinner et al, 2005). This familial type of thyroid carcinoma usually originates as multifocal C-cell hyperplasia, its progression to MTC is extremely variable, and may take several years (Carling, 2005).…”
mentioning
confidence: 99%